Logistics Management as a Tool to Achieve Competitive Advantages of the Enterprise Trade - Victoria V. Prokhorova; Oksana N. Kolomyts; Alyona I. Nenasheva; Nickolay A. Sholukha; Pavel G. Vashchenko (International Review of Management and Marketing, 2016)
The need for logistics management explained convent-house reasons, among which we distinguish the main. One of them – the development of competition caused by the transition from a seller’s market to a buyer’s market. Cash invested in the sphere of distribution, began to influence the position of the supplier on the market is much stronger than the same money invested in the sphere of production. The logistically organized material leading chains cost of goods delivered to the final consumer was lower than the cost of the same goods held by the traditional way. Emerging difference provides the participants a competitive advantage, not dependent on the size of included capital, and the ability to organize the logistics process. In addition, using the logistics providers can guarantee the delivery on time the right amount of product required quality and represent for the consumer is much more valuable than suppliers that the reliability of such assurances do not provide.